"It's a bit of freedom away from home and cleaning all the time": Schooling, gender relations and Gypsy communities in England. Issue 5 (7th May 2019) - Cudworth, Dave
Abstract : Purpose: Much has been written over the past 50 years about the concerns associated with the educational underachievement of Gypsy children in England. This work has usually focussed on ethnicity and mobility as key factors that affect school attendance. However, it is only relatively recently that a concern with gender relations has entered the debate. Therefore, the purpose of this paper is to provide an empirically driven contribution to this fledging area of enquiry. Design/methodology/approach: This paper draws on semi-structured interview material and a focus group discussion about the educational experiences and aspirations of three mothers and six young women from the community. Further, interview materials were collected from two head teachers with Gypsy children in their schools and two Traveller Education Support Staff. Findings: This paper finds how educational "public" space is providing a place for girls and young women to think differently and even begin to challenge the gender regimes embedded within the "private" space of their communities. Originality/value: In line with the idea that space and place are fundamental in formulating gender relations, this paper frames this phenomenon within a socio-spatial context.